Security, commercial and monetary policies - Hugh Corbet (Intereconomics, 1974)
This article discusses the frustrations both sides of the Atlantic regarding security, commercial and monetary policies. It suggests, however, that with the European Community, Japan and the USA all in difficulties together they might now possess the political will to arrest through negotiations a threatening return to discriminatory policies.
Keywords: 330; Foreign Trade